How nomadic pastoralists in Somalia's mudug region adapt to climate and conflict shocks - Abdullahi, Said; Takaindisa, Joyce (2025)
This report examined the key drivers of these conflicts and proposed actionable, context-specific solutions to strengthen peacebuilding efforts in Mudug and across Somalia. It drew on 25 key informant interviews with nomadic pastoralists, clan elders, government officials, humanitarian actors and security experts. The interviews were conducted in Mudug in March 2025, with follow-up interviews conducted by phone through April 2025.